"A social worker first and foremost": The motivation and experiences of recently qualified social workers in posts not requiring social work registration in England. (29th August 2016) - Scholar, Helen
Abstract : This article reports findings from a qualitative study based on interviews with recently qualified social workers (within the last five years) employed in positions not requiring social work registration and qualification. It discusses the motivations and experiences of recently qualified social workers in posts not requiring social work registration and the issues that they identify as important in maintaining an individual and collective social work identity.